Cystophora cristata - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Cystophora cristata (Erxleben, 1777). Syst. Regn. Anim., 1:590. TYPE LOCALITY: S. Greenland and Newfoundland. DISTRIBUTION: N. Atlantic and Arctic oceans, from Newfoundland (Canada) to S. Greenland, Svalbard and Novaya Zemlya (U.S. S.R.). Occasionally south to Portugal and Florida (U.S.A.). ISIS NUMBER: 5301413002001001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 286, DOI: 10.5281/zenodo.7352980